Detection of rtxA gene and other virulence genes in non-O1 and non-O139 Vibrio cholerae isolated from ornamental fishes in India - SWAMINATHAN, THANGARAJ RAJA; RATHORE, GAURAV; SOOD, NEERAJ; LAKRA, WAZIR SINGH (The Indian Journal of Animal Sciences, 2011)
Vibrio cholerae non-O1 and non-O139 serogroups (16) were isolated from koi carp, goldfish and aquarium water during 2004–2005. All the isolates were confirmed by amplifying the 300bp fragment in the 16S–23S rRNA intergenic spacer region. By several PCR assays, it was determined that none of the non-O1 and non-O139 isolates were positive for ctxA, zot, ace and tcpA genes. But all the isolates were positive for the toxR, ompU and rtxA genes.